Serratia marcescens: A Rare Cause of Recurrent Implantable Cardioverter Defibrillator Site Infection - S. Hawkey; AM. Choy (Case Reports in Cardiology)
We present a unique case of a patient who experienced recurrent infections of his implantable cardioverter defibrillator (ICD) site with the bacterium Serratia marcescens. This report highlights the virulence of this bacterium, its resistance to antibiotic therapy, and its ability to remain latent for prolonged periods between episodes of sepsis. It also demonstrates the merits of reimplanting devices at different sites in the context of Serratia marcescens infection.